Public/private transitions and firm financing - Kim P. Huynh; Teodora Paligorova; Robert Petrunia (Bank of Canada, 2013)
A large body of empirical literature investigates differences in financing structures across firms. Private firms' financing receives little attention due to the lack of data. Using administrative confidential data on the universe of Canadian corporate firms, we compare financing relationships for private and public firms. Leverage ratios are lower for public firms and the difference is almost entirely driven by private firms' stronger reliance on short-term debt. We also find that private and public firms' debt financing responds differently to industry shocks. In periods of positive industry shocks, private firms rely more on long-term debt than public firms, while the former use more short-term debt when industry conditions deteriorate.
Keywords: G30; L11; 330; Financial markets; Credit and credit aggregates